Drugs used in incident systemic lupus erythematosus – results from the Finnish nationwide register 2000–2007. (May 2016) - Elfving, P; Puolakka, K; Kautiainen, H; Virta, L J; Pohjolainen, T; Kaipiainen-Seppänen, O
The objectives of the study were to examine the initial, first-year anti-rheumatic outpatient therapy in patients with incident SLE, as well as the concomitant use of drugs for certain comorbidities, compared to the use in the general population. The Finnish nationwide register data on special reimbursements for medication costs was screened to identify the inception cohort of 566 adult SLE patients (87% females, mean age 46.5 ± 15.9 years) over the years 2000–2007. The patients were linked to the national Drug Purchase Register. Of those, 90% had purchased at least once some disease-modifying anti-rheumatic drugs (DMARDs) during the first year. Hydroxychloroquine was the most common (76%), followed by azathioprine (15%) and methotrexate (13%). With the exception of increase in mycophenolate mofetil, the proportions remained stable over the whole study period 2000–2007. Drugs for cardiovascular diseases, dyslipidemia, diabetes mellitus, hypothyroidism and obstructive pulmonary disease were more frequently purchased than in the sex- and age-adjusted population, with rate ratios ranging from 1.6 to 7.8. Over the years 2000–2007, almost all the patients with incident SLE in Finland started with a DMARD. Higher percentages of SLE patients were on medication for several common chronic diseases than in the population as a whole.